Normal distribution of presenilin-1 and nicastrin in skeletal muscle and the differential responses of these proteins after denervation - Sakuma, Kunihiro; Nakao, Ryuta; Yamasa, Yuka; Yasuhara, Masahiro (Biochimica et biophysica acta, 2006)
Presenilin-1 and nicastrin, two components of γ-secretase associated with Alzheimer's disease plaques, are present in the synapses of the brain and in various peripheral organs, including skeletal muscle. In the present study, we examined the expression pattern of presenilin-1 and nicastrin in normal and denervated hindlimb muscles of the rat. Using immunohistochemical approaches, we found that presenilin-1 and AChRα was co-localized at the neuromuscular junction in the normal skeletal muscles of rats. The immunoreactivities of both presenilin-1 and nicastrin were also observed at the sarcolemma of muscle fibers. We discovered that presenilin-1 mRNA and its protein are upregulated after denervation of the soleus and tibialis anterior muscles. Furthermore, clear co-localization between presenilin-1 and DAPI, but not nicastrin, was noted in several myonuclei in the denervated muscles. We recognized a few fibers possessing both ubiquitin and presenilin-1 protein in the cytosol. The amount of presenilin-1 in the nucleus and membrane fraction was more abundantly expressed in the denervated muscle fibers. In contrast, no significant difference in the nicastrin protein level was observed between normal and denervated muscle fibers. These data suggest that enhanced presenilin-1 protein may play a role in the degeneration and regeneration of skeletal muscle.